Голодомор 1932–1933 років очима українців діаспори (документи з фондів ЦДАВО України) - Берковський, В.; Григорчук, Н.; Петрук, О. (Архіви України, 2008)
The publication contains the documents from the fonds of the Central State
Archives of Supreme Bodies of Power and Government of Ukraine reflecting the
Ukrainian diaspora’s attitude towards the 1932–1933 Famine in Ukraine. It includes
little-known facts related to the so-called “aid actions”, appeals to international
community, Ukrainian emigration’s protests against the criminal Soviet policy
in Ukraine in 1932–1933. The publication is supported with the documents of
political and non-government organizations, well-known Ukrainian public figures
in Czechoslovakia, the USA, Rumania, Poland, France.